Injury-related mortality audit in a regional trauma center at Puducherry, India - Radjou, Angeline Neetha (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: There is an alarming trend of injuries leading to poor outcome of victims in India. OBJECTIVE: To study the profile of patients who died due to trauma and to identify factors involved in both pre-hospital and hospital care. MATERIALS AND METHODS: A hospital-based study was performed at a trauma center in Puducherry from June 2009 to May 2010. Patients who had at least one sign of life on admission and later died were included. The demographic characteristics, injury mechanism, nature and site of injury, influence of alcohol, pre-hospital time and care, distance traveled, number of referrals, time spent in study hospital, cause of death, and missed injuries revealed at post mortem were noted. RESULTS: Of the 204 fatal cases, most were between 25-65 years of age (77%); sustained injuries over weekends (36%) and between 4 pm and midnight (41%); had at least one halt in a medical facility before reaching definitive care (56%); and died within a week (63%). Adults (25-65 y) sustained most injuries (77%) on two wheelers. In those aged over 65 years, 79 percent were pedestrians. Road traffic injuries were responsible for 82 % of deaths; 16 percent were reportedly under the influence of alcohol at the time of injury. Mean delay from the time of accident to admission was 14.9 hours and median distance traveled was 30 kilometers. Head injury was the most common (66%) cause of death. Post mortem revealed skull fractures (37%), while missed injuries were noted in 8 percent, mostly involving the cervical spine and chest wall. CONCLUSION: The problem of trauma care needs to be addressed urgently in this part of southern India to reduce mortality and morbidity.